Estudo de otimização do aproveitamento hídrico superficial no alto curso do rio Uberaba, UPGRH GD8 - Costa, Emiliano Silva (2015)
The water resources have always been of fundamental importance for the survival of the species. Over time, these resources have gained greater importance due to the economic development of Brazil and the world, with the multiplicity of its uses, for example public supply, crop irrigation, power generation, watering livestock, among others. In order to minimize the pressure on water resources, management tools have been developed to support the planning and management of water resources within the watershed. Therefore, this study aimed to explore alternatives optimization of surface water use in the upper reaches of the Uberaba river, belonging to Unit Planning and Management of Water Resources in the Baixo Rio Grande - UPGRH GD8. In the study of the availability of water it was found that the replacement of the annual flow Q7,10 monthly basis for calculation showed increased flow available for most of the year, the most significant being in the month of February, 2488% increase in water availability, while the month of October showed 47.22% less water availability compared with the annual Q7,10. Within the criteria for granting study grants, the criterion of 50% of the monthly Q7,10 showed the highest increase in water availability. The water balance held in the Environmental Protection Area (APA) through AQUATOOL tool, from 2004 to 2014, the results confirmed the need to implement an accumulation reservoir to meet the deficit in the public water supply of the city of Uberaba - MG. Seen it, to start the simulation, the reservoir was installed upstream of the current collection system existing trickle, to reduce the effects of human activities, so that their design resulted in a volume of 2.146 hm³ to answer a flow supply of 1.334 m³ / s estimated for the horizon of population growth 30 years. After the location and sizing of the accumulation reservoir, for the same period 2004 to 2014 were simulated two scenarios to verify the variation of the reserved volume, the public supply deficit and residual flow downstream of the reservoir. In Scenario 1 it was considered only the currently registered with the grant IGAM and cancellation of water transposition of the river course, while in Scenario 2 was considered as granted flow, maximum availability in each sub-basin belonging to APA. Both scenarios presented variation in volume during the simulated period, but were favorable to the supply deficit in the public supply, allowing the disposal of current river water transposition system Claro river to Uberaba river. As for the residual downstream of the reservoir, the two scenarios did not meet the legislation in the years 2013 and 2014, and they did not guarantee a residual 50% of Q7,10. In general, the AQUATOOL tool achieved satisfactory results in studies conducted in the APA and that can assist management bodies in this area in decision-making.